Progress in polymeric separators for lithium ion batteries. Issue 109 (21st October 2015) - Zhang, Hong; Zhou, Ming-Yong; Lin, Chun-Er; Zhu, Bao-Ku
Abstract : This study reviews the recent developments and the characteristics of polymeric separators used for lithium ion batteries. Abstract : This study reviews the recent developments and the characteristics of polymeric separators used for lithium ion batteries. According to the structure and composition of the separators, they are broadly divided into four types: (1) polyolefin microporous separators, (2) heterochain polymer microporous separators, (3) polymer electrolytes and (4) non-woven separators. In particular, polymer electrolytes were defined as one category of separators for convenient description in this review; these feature intermediates between the two electrodes and possess transport properties comparable with the separator in liquid LIBs. For each category, the structure, characteristics, modification, and performance of separators are described. Finally, guidelines for further improvements in this research are outlined.